2022
DOI: 10.3390/d14020143
|View full text |Cite
|
Sign up to set email alerts
|

How Many Edible Insect Species Are There? A Not So Simple Question

Abstract: Insects used as food and medicine are receiving increased attention. There is a need to scrutinise recent estimates of which and how many insect species are used as we have noticed inappropriate assessments and overestimations. We review the contemporary list of edible insects of the world published online by Wageningen University and compiled by Ijde Jongema since it is widely used in the literature. Each of the 2403 entries were scrutinised, including checking name validity, verifying insect usage in cited r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 38 publications
0
11
0
1
Order By: Relevance
“…The study revealed parasites in 244 out of 300 examined insect farms. Interestingly, 206 of the cases had parasites that were pathogenic for insects only; 106 had parasites pathogenic for animals; and in 91 cases, parasites were pathogenic for humans ( 6 ). However, in humans, before being consumed, edible insects must first undergo one of four common processes: boiling, drying, toasting, or frying ( 103 ), which can kill pathogens associated with the edible insect.…”
Section: Edible Insects As a Reservoir Of Diseasesmentioning
confidence: 99%
“…The study revealed parasites in 244 out of 300 examined insect farms. Interestingly, 206 of the cases had parasites that were pathogenic for insects only; 106 had parasites pathogenic for animals; and in 91 cases, parasites were pathogenic for humans ( 6 ). However, in humans, before being consumed, edible insects must first undergo one of four common processes: boiling, drying, toasting, or frying ( 103 ), which can kill pathogens associated with the edible insect.…”
Section: Edible Insects As a Reservoir Of Diseasesmentioning
confidence: 99%
“…More study is needed to find a comprehensive practical and cheap approach to minimize the painful bites faced by maintenance staffs in occupied plant canopies. [79,7] herbivory assists nutrient cycle See [139,140,141,142,143,144] mixed crops, luxury woods See [79,7,145] * New Britain Papua New Guinea; **NA: not available -***Invasive species 1 available online by 2009; 2 see (Yang, 1984) Eventhough the Asian weaver ant successful application in cocoa plantations in Malaysia was proven, [99], its final adoption was lately abandoned due to O. smaragdina aggressive behavior [20,21]. This nuisance factor is impossible to be eluded since man-made intervention is permanent.…”
Section: Benefits and Challengesmentioning
confidence: 99%
“…Currently, there are around 2111 species of edible insects (Jongema, 2017; Lanzerath & Schurr, 2022). However, Van Itterbeeck and Pelozuelo (2022) recalculated the number based on critical assessment and reported that there could be 1161 species of insects for food and 81 species of insects for medicinal purposes. The commonly used categories of edible insects are well established.…”
Section: Introductionmentioning
confidence: 99%